Recovery of Infectious Human Norovirus GII.4 Sydney From Fomites via Replication in Human Intestinal Enteroids - Overbey, Katie N.; Zachos, Nicholas C.; Coulter, Caroline; Jacangelo, Joseph; Schwab, Kellogg J. (Frontiers in Cellular and Infection Microbiology, 2021)
Contamination of fomites by human norovirus (HuNoV) can initiate and prolong outbreaks. Fomite swabbing is necessary to predict HuNoV exposure and target interventions. Historically, swab recovered HuNoV has been measured by molecular methods that detect viral RNA but not infectious HuNoV. The recent development of HuNoV cultivation in human intestinal enteroids (HIEs) enables detection of infectious HuNoV. It is unknown if the swabbing process and swab matrix will allow for cultivation of fomite recovered HuNoV. We used HIEs to culture swab-recovered HuNoV GII.4 Sydney from experimentally infected surfaces – a hospital bed tray (N=32), door handle (N=10), and sanitizer dispenser (N=11). Each surface was swabbed with macrofoam swabs premoistened in PBS plus 0.02% Tween80. Swab eluate was tested for infectious HuNoV by cultivation in HIE monolayers. Infectious HuNoV can be recovered from surfaces inoculated with at least 105 HuNoV genome equivalents/ 3 cm2. In total, 57% (N=53) of recovered swabs contained infectious HuNoV detected by HIEs. No difference in percent positive swabs was observed between the three surfaces at p=0.2. We demonstrate that fomite swabbing can be combined with the HIE method to cultivate high titer infectious HuNoV from the environment, filling a significant gap in HuNoV detection. Currently, high titers of HuNoV are required to measure growth in HIEs and the HIE system precludes absolute quantification of infectious viruses. However, the HIE system can provide a binary indication of infectious HuNoV which enhances existing detection methods. Identification of infectious HuNoVs from swabs can increase monitoring accuracy, enhance risk estimates, and help prevent outbreaks.